Mechanism of deactivation processes of excited iron(III) thiocyanato complexes with benacen-type ligands - Jozef Šima; Mário Izakovič; Marián Žitňanský (International Journal of Photoenergy)
The complexes [Fe(4-R-benacen)(CH3OH)(NCS)], where 4-R-benacen2− are tetradentate open-chain N,N′-ethylenebis(4-R-benzoylacetoneiminato) N2O2-ligands (R=H, Cl, Br, OCH3), are redox stable in the dark in methanolic solutions. Irradiation of the complexes into intraligand and/or ligand-to-metal charge-transfer bands induces a series of photophysical and photochemical deactivation processes leading to Fe(II) and CH2O as final products in a 2:1 molar ratio. Formation of polystyrene containing bonded NCS group when irradiating the complexes in the presence of styrene monomer used as a radical scavenger indicates that the primary photoreduction of Fe(III) to Fe(II) is accompanied by the oxidation of NCS− ligand to •NCS radical. 4-R-benacen-ligands behave as an innocent moiety virtually not participating in the photoinduced redox processes. The quantum yield of Fe(II) formation ΦFe(II) decreases significantly with increased wavelength of the incident radiation, and is slightly influenced by the peripheral groups R of the 4-R-benacen-ligands.